Pikobar and Jabar Saber Hoaks: Dynamics of E-Government Implementation in Preventing Bureaucratic Pathology in West Java - Alghifari, Gilang Arya; Sundawa, Dadang (Jurnal Mamangan, 2023)
The pandemic has implications for all aspects of human life, including the bureaucratic aspect. In this case, the reality experienced in the bureaucratic process in West Java reflects a lack of transparency, corruption and tortuous procedures, and extortion. This research aims to find a solution to bureaucratic pathology in West Java by using a digital government innovation. The research method used is Qualitative with a Case Study Approach, which aims to discover the West Java government's innovations in prevention to create an efficient bureaucratic system amidst the momentum of the pandemic. The results of the study show that the West Java Government has succeeded in innovating in preventing Bureaucratic Pathology by optimizing Government Digitalization or E-Government, namely creating the Jabar Saber hoaks and PIKOBAR Programs, which aim for various uses for the people of West Java during the Covid-19 period as well as developing an application for reporting the number of recoveries and died and spread validity news related to the issue of Covid-19 and other social problems in the Pandemic era.